Green Synthesis of 2-Mercapto 5,6-Dihydro-4H-1,3-Thiazines via Sequential C–S Couplings - Wenjie Liu; Shuo Wang; Li Pan; Xiaojing Bi; Enxue Shi (Molecules)
The six-membered N,S-heterocyclic 1,3-thiazines and their derivatives are widely acknowledged as pharmaceutical molecules with a wide range of biological activities. In this study, we developed a unique thiol-involved cascade reaction that enables the efficient construction of the 5,6-dihydro-4H-1,3-thiazine scaffold through consecutive intermolecular thiol-isothiocyanate and intramolecular thiol-halogen click reactions. Structurally diverse 2-mercapto dihydrothiazines including three antitumour candidates of bis-dihydrothiazines were readily obtained in high yields from the readily available thiols and 3-chloroisothiocyanate in the green solvent EtOH/H2O (1:1) using K2CO3 (0.6 equiv.) as the base. Between the two synthesis procedures investigated, the microwave-assisted reaction generally behaved more efficiently than that under routine heating conditions. Furthermore, DFT calculation confirmed the sequential addition–substitution mechanism. This cascade C–S coupling reaction methodology offers several advantages, including rapid completion, high reliability, easy purification, and benign conditions.